Kryzys lat 2007–2009 i luka informacyjna w sektorze finansowym - Włodzimierz Siwiński (Management and Business Administration. Central Europe, 2013)
Purpose: The paper aims at identifying the major information gaps related to the financial sector that have emerged during the last years, including the explanation of the reasons and consequences of these gaps.Methodology: The analysis is conducted using the descriptive methodology based on real developments in the financial sector. This analysis identifies substantial institutional changes within the financial sector combined with the introduction of new financial instruments that significantly increased information gaps related to financial developments.Findings: We found that one of the main reasons for the breakdown in the financial liquidity market was the sudden buildup of a systemic risk caused, among other things, by substantial information gaps and limitations in the transparency of financial markets. The low transparency of the financial markets has been caused by institutional changes and new financial instruments introduced within the financial sector. They were introduced by the financial institutions themselves to facilitate very risky financial activities that were very profitable for them in the short term, but – as it occurred – very disruptive for the whole financial system and the whole economy in the longer term.Research limitations: The analysis is limited only to the consideration of the causes and consequences of statistical gaps substantially reducing the transparency of the financial sector. A more comprehensive project should also explore and provide an appropriate proposal for remedy data and – even more important – a proposal to set up a macroprudential policy framework.Originality: The original contribution of the paper is the link between specific institutional changes within the financial sector as well as new financial instruments and the emergence of particular information gaps.